Postmodern tendencies in the russian poetry of the “Silver Age” - Chornyi, I. V.; Чорний, І. В.; ORCID: https://orcid.org/0000-0001-6079-1746; Pertseva, V. А.; Перцева, В. А.; ORCID: https://orcid.org/0000-0002-5203-761X; Chorna, V.; Чорна, В.; ORCID: https://orcid.org/0000-0002-7288-9043; Horlova, О.; ORCID: https://orcid.org/0000-0002-7702-3222; Shtepenko, O.; et al. (Postmodern Openings. - 2021. - Vol. 12, № 4. - P. 124-140, 2021)
У статті вперше аналізуються окремі аспекти російської поезії «Срібного століття» з метою виявлення рудиментів чи рис, притаманних постмодерністській творчій парадигмі.

For the first time, the article analyses certain aspects of Russian poetry of the “Silver Age” in order to identify the rudiments or features which are characteristic of the postmodern creative paradigm. It is noted th at a number of poets almost do not have any postmodernist tendencies. Despite the fact it is proved that postmodernism denies the personality - centric and aesthetically oriented concept of modernism, it nevertheless arose on the basis of modernism and has s harpened evolutionary features formulated in the first half of the 20th century. The article aims to prove a hypothesis that arises in the authors during a preliminary perceptual reading of the poets` works of the “Silver Age”: in the early 20th century. S poradically and consistently in individual authors can be observed irony, play, reconstruction and performance as precursor of postmodernist creative thinking. Specialties of the Russian poetry of the “Silver Age”, which directly correlate with postmoderni st tendencies of the second half of the 20th century is not a description itself, but the realization of reality, ambivalence, as well as following the linguistic and figurative, conceptual, motive levels of gradual transitions between the paradigms of “sy mbolism – modernism” and “modernism – postmodernism”. The international significance of the article is that the material of one of the Eastern European literatures has proved the existence of postmodern (quasi - postmodern) features in the first half of the 20th century for the first time, which can serve as a deeper research in the field of literary typology, continuity; culturology and anthropology.

В статье впервые анализируются отдельные аспекты русской поэзии «Серебряного века» с целью выявления рудиментов или черт, характерных для постмодернистской творческой парадигмы.
Postmodern Tendencies in the Russian Poetry of the “Silver Age” / Chornyi, I., Pertseva, V., Chorna, V. and oth. // Postmodern Openings. - 2021. - Vol. 12, № 4. - P. 124-140. - DOI: https://doi.org/10.18662/po/12.4/364.
Chornyi, I., Pertseva, V., Chorna, V., Horlova, O., Shtepenko, O., & Lipisivitskyi, M. (2021). Postmodern Tendencies in the Russian Poetry of the “Silver Age”. Postmodern Openings, 12(4), 124-140. https://doi.org/10.18662/po/12.4/364
Keywords: Мова. Мовознавство. Літературознавство. Language. Linguistics. History and Criticism of Literature. Язык. Языкознание. Литературоведение; Наукові публікації. Scientific publications. Научные публикации; postmodernist trends; literary continuity; origins of intertextuality; aesthetic categories; mytho logical figures; “Silver Age”; publikatsii u WoS; "Срібне століття "; "Серебряный век"; "Срібна доба"; Росія; Россия; Russia